Dan Penerapan Standar Akuntansi Berbasis Akrual Terhadap Kualitas Laporan Keuangan Pengadilan Agama Batam - Tri Irma Ningrum (JURNAL EKOBIS DEWANTARA, 2018)
This study aims to examine the effect of human resource quality, utilization of information technology, and the implementation of accrual government-based accounting standards on the quality of financial statements of religious courts of Batam. We the primary data from contains 47 questionnaire The population all employees who work in the religious court of Batam. We use saturated sampling method. We find that multiple linear regression equation is Y = 39,882 + 0,080X1 + 0,0170X2 + 0,477X3 + e. The implementation of accounting standards of government based on accruals has a significant effect on the quality of financial report of religious court of Batam, while the quality of human resources, and the utilization of information technology has no significant effect on the quality of financial report of the religious court of Batam. Keywords: Quality of Human Resources, Utilization of Information Technology, Implementation of Accrual Based Accounting Standards, Quality of Financial Relatif, Religious Count of Qountum